Trauma surgery in an acute care hospital: Critical analysis of systematic surgical exploration - Bado, Joaquín; Trostchansky, Julio; Machado, Fernando (Cirugía del Uruguay, 2006)
Systematic surgical exploration for penetrating abdominal wounds is considered, in the Maciel Hospital the Gold standard for diagnosis and therapy. In order to analyze the rate of unnecessary surgeries (including among them those that do not manage to identify lesions, and those that having identified them, had no therapeutic value), a retrospective study was conducted on a series of 238 along a period of 2 years and 5 months (October 2001 to March 2004) in the Emergency Service of Maciel Hospital. Sharp instrument wounds accounted for 67, of which 22 (33%) were unnecessary laparotomies. Of the 59 laparotomies performed in the treatment of firearm wounds, 11 were unnecessary (18,6%).. As a conclusion it may be said that systematic surgical exploration in the group of patients with penetrating abdomen wounds, particularly those caused by sharp instruments, are the cause of a high rate of unnecessary laparotomies patients, who under went surgery due to trauma,